Current Status and Distribution of Reptiles of Sindh - Khan, Muhammad Zaheer; Ghalib, Syed Ali; Siddiqui, Saima; Siddiqui, Tanveer Fatima; Farooq, Rehana Yasmeen; Yasmeen, Ghazala; Abbas, Darakhshan; Zehra, Afsheen (Journal of Basic & Applied Sciences, 2012)
In Sindh province, total 103 species of reptiles comprising of 42 Lizards, 45 Snakes, 14 Turtles, 1 species each of Tortoise, Crocodile and Gavial has been recorded. 13 key areas for the reptiles have been identified in Sindh along with three important sites viz. Karachi coast, Deh Akro Wildlife Sanctuary and Nara Wetland Complex. Some reptiles are under threat due to large scale exploitation for skin, medicinal use and as food item. Marine Turtles are threatened mainly due to habitat degradation. The common species include Indian Fringe-toad Lizard, Indian Sand Swimmer, Indian Garden Lizard, Sindh Sand Gecko, Desert Monitor and Saw-scaled Viper. Eight species are threatened and 16 species are of special conservation interest and need to be conserved.